Green Synthesis of ZnO Particles using Jasmine Tea Extract from Commercial Tea Bags - Yayat, Hasna Noer Agus; Martina, Desti; Salis, Witri Aini; Maulida, Nafisa Rizki (ALCHEMY:Journal of Chemistry, 2025)
Zinc oxide refers to an inorganic compound functioning as a semiconductor, recognized for its wide-ranging potential and current usage in multiple domains, such as for antibacterial purposes. The formation of zinc oxide using a sustainable synthesis route, notably via plant-based extracts, has become an attractive alternative due to its eco-conscious and economical nature. This study synthesized ZnO particles with zinc acetate as the starting material and jasmine tea extract derived from commercial teabags acting as the reducing agent in two ratio variations (Z1 and Z2). The produced particles underwent characterization via XRD, SEM-EDX, PSA, UV-Visible spectrophotometry, and their antibacterial activity was evaluated using a microdilution method to find the MIC point. The result showed that both ZnO particles adopt a wurtzite crystal, and the morphology possesses a round morphology with an estimated diameter of 500 nm. Optical properties of ZnO were also observed, yielding results of 3.9 eV and 3.2 eV. Antimicrobial potency testing was additionally performed on S. aureus and E. coli with an MIC value of 1000 ppm.